Activity period study and of the behaviour displayed by gastropod Zonitoides arboreus (Say, 1816) (Pulmonata, Zonitidae) in laboratory - Pilate, Vinícius José; Vargas, Tércia; Silva, Lidiane Cristina da; Souza, Bruna Aparecida de; Chicarino, Evelyn Durço; Bessa, Elisabeth Cristina de Almeida; Sousa, Bernadete Maria de (Revista Nordestina de Zoologia, 2015)
The knowledge of the behavior of terrestrial molluscs is important for the development of conservation and population control strategies. Aimed verify the activity period and behavioral acts that make up the ethogram of the species Zonitoides arboreus, were performed direct observations of 30 snails criated in terrariums, through the scanning method, recording the behavioral acts at regular intervals of 20 minutes, totaling 24 hour continuous observation. Five behavioral acts were recorded: rest, move, be buried, food and explore. Was verified statistical difference between activity and rest, being the acts that characterize the rest bahaviour of animals more frequent than the other acts. The species showed predominantly nocturnal activity period. The temperature and relative humidity did not influence the activity of this species.